National Unique Features of The Country House Concept - Cherednyk, Lyudmyla; Shevchenko, Elena; Bondar, Nataliia (International Journal of Engineering and Technology, 2018)
The article highlights peculiarities of verbalization and semantic content of the country house (KHATA) concept in the Ukrainian literature, in the works of Grigoriy and Grigir Tyutyunnyk in particular. It systematizes linguistic views on the nature of linguomental constructions, provides definitions of the main linguo-cognitive categories; basic mentality concept is brought to the fore, as a fixed in the dictionary notion, meaningful to a culture with ethnospecific semantic shade, which accumulates relatively stable ideas related to socio-historical experience and value orientations of the nation. The paper studies the correlations between linguistic and artistic concepts, actualizes linguistic and cultural aspects of realia that embody life, world-view, the Ukrainian countrymen’ culture. Attention is paid to the configuration of lexical and phraseological units expressing the Ukrainian culture fundamental concepts  and world perception of the word painters; their role in the figurative system and idiostyle paradigm, taking into account metaphorical expression, contextual surrounding, ethnocultural and peculiar authorial symbols is investigated. The specificity of the prose writing, which consists in the frequent use of archaic, colloquial, dialectal words and constructions, specifically Ukrainian phraseology and etiquette formulas that ethnically color the concept of KHATA, are pointed out. PAINTED STOVE, EMBROIDERED RUSHNYK, HOLY PICTURES, ASTERS and STORK NESTS on the roof are peculiar for the Ukrainian KHATA. For a COUNTRYMAN it was not just a living place, a place of initiation and ritualization, it was his BEGINNING, GENEALOGY, FATHERLAND.